Natural resources and sovereign expropriation - Fridrik Mar Baldursson; Nils-Henrik M. von der Fehr (University of Oslo, Department of Economics, 2015)
A government wants to exploit a renewable resource, yielding a timevarying flow of rent, by leasing it at a fixed rate. Leasing contracts can be expropriated before expiration, albeit at a cost. To minimise transactions costs and avoid the 'resource curse' the government would prefer to enter into an infinitely long contract (i.e. sell the resource), if it could commit not to expropriate. However, with finite costs of expropriation credible commitment is impossible: the government either enters into finite contracts, expropriates with positive probability or does both. The value of the resource to the government is increasing in the cost of expropriation, but decreasing in the variability of the resource rent.
Keywords: H13; Q2; D86; 330; natural resources; sovereign expropriation; optimal contract length